Effects of different levels of flooding and additional application of two nutrients on boro rice (Binadhan-8) in saline soil - Raihan, Md Zahir; Hasan, Md Saeed; Md. Moslehuddin, Abu Zofar; Tarafder, Md Mahbubul Alam; Haque, Md Ekramul (Research in Agriculture Livestock and Fisheries, 2015)
A field experiment was conducted at Kalikapur village of Kaliganj upazila under Satkhira district in order to observe the effects of flooding duration and additional application of K and S on transplanted boro rice cv. Binadhan-8 during January - May 2013. The experiment was laid out in a split-plot design where the main plots comprised of five flooding levels viz. continuous flooding (W1), flooding for 10 days (W2), flooding for 20 days (W3), flooding for 30 days (W4), flooding for 40 days (W5), and the sub-plots of four additional (over the recommended dose) nutrients rates viz. S43 + K25 (T1), K38 (T2), S32 + K38 (T3), and K50 (T4), with three replications. The duration of flooding showed significant positive effect on the yield and yield components of boro rice cv. Binadhan-8. The highest values for plant height (106.8 cm), panicle length (28.4 cm), number of plants hill-1 (15.3), grain yield (4.8 t ha-1) and straw yield (6.5 t ha-1) were recorded in continuous flooding (W1) while these values were decreased with the decrease in the duration of flooding from 40 days to 10 days. Additional application of K and S also significantly influenced all of the parameters. Results revealed that the highest values for plant height (102.8 cm), panicle length (26.6 cm), plants hill-1 (15.4), 1000-grain weight (23.9 g), grain yield (4.8 t ha-1) and straw yield (6.1t ha-1) were obtained from T3 where S and K were applied @ 32 and 38 Kg ha-1 in addition to the recommended fertilizer rate. The interaction of flooding and nutrients significantly manipulated the yield and yield attributes. Due to interaction of flooding and nutrients, the highest growth and yield was observed in continuous flooding with S32 + K38 (W1T3). The results indicated that the flooding with fresh water and use of additional nutrients (K and S) had a remarkable effect in growing boro rice cv. Binadhan-8 in saline soils of Bangladesh. Res. Agric., Livest. Fish.2(3): 439-443, December 2015